BUSINESS TRAINING AS A DETERMINANT OF MSME PERFORMANCE IN KULON PROGO, INDONESIA - Akhid Nurhayati; Ahmad Maruf; Imamudin Yuliadi (UNIVERSITAS MUHAMMADIYAH METRO, 2026)
Micro, Small, and Medium Enterprises (MSMEs) play a significant role in the Indonesian economy but continue to face structural constraints such as limited human resource capacity, market access, and policy support. This study aims to identify the structural position of business training within the MSME performance system in Kulon Progo Regency. The research employs a qualitative structural design using the MICMAC (Cross-Impact Matrix Multiplication Applied to Classification) method. Data were collected through Focus Group Discussions (FGDs) involving 18 stakeholders representing government institutions, MSME practitioners, business associations, and academic experts. A total of 16 variables representing policy support, internal capacity, and business environment dimensions were analyzed using direct and indirect influence matrices to map the level of influence and dependence among variables. The results show that business training emerges as one of the key driving variables in the MSME performance system. Training not only improves human resource quality but also strengthens innovation capability, growth orientation, and managerial practices among MSMEs. These findings indicate that capacity building through business training generates systemic effects that contribute to improving competitiveness and long-term business sustainability. Therefore, MSME development policies at the regional level should position business training as a strategic priority integrated with mentoring programs, financial facilitation, and market access support.